Biocrust‐forming mosses mitigate the negative impacts of increasing aridity on ecosystem multifunctionality in drylands. Issue 4 (9th October 2015) - Delgado‐Baquerizo, Manuel; Maestre, Fernando T.; Eldridge, David J.; Bowker, Matthew A.; Ochoa, Victoria; Gozalo, Beatriz; Berdugo, Miguel; Val, James; Singh, Brajesh K.
Summary: The increase in aridity predicted with climate change will have a negative impact on the multiple functions and services (multifunctionality) provided by dryland ecosystems worldwide. In these ecosystems, soil communities dominated by mosses, lichens and cyanobacteria (biocrusts) play a key role in supporting multifunctionality. However, whether biocrusts can buffer the negative impacts of aridity on important biogeochemical processes controlling carbon (C), nitrogen (N), and phosphorus (P) pools and fluxes remains largely unknown. Here, we conducted an empirical study, using samples from three continents (North America, Europe and Australia), to evaluate how the increase in aridity predicted by climate change will alter the capacity of biocrust‐forming mosses to modulate multiple ecosystem processes related to C, N and P cycles. Compared with soil surfaces lacking biocrusts, biocrust‐forming mosses enhanced multiple functions related to C, N and P cycling and storage in semiarid and arid, but not in humid and dry‐subhumid, environments. Most importantly, we found that the relative positive effects of biocrust‐forming mosses on multifunctionality compared with bare soil increased with increasing aridity. These results were mediated by plant cover and the positive effects exerted by biocrust‐forming mosses on the abundance of soil bacteria and fungi. Our findings provide strong evidence that the maintenance of biocrusts is crucial to buffer negative effects of climate change on multifunctionality in global drylands.